Pengaruh Kebijakan Dividen, Kebijakan Hutang Dan Profitabilitas Terhadap Nilai Perusahaan: Studi Pada Perusahaan Yang Tergabung Dalam LQ-45 Di Bursa Efek Indonesia Periode 2019-2022 - Deni Sapitra; Agus Solikhin; Ida Masriani (Universitas 45 Surabaya, 2024)
This study aims to determine the effect of dividend policy, debt policy, and profitability on firm value in companies included in the LQ-45 index on the Indonesia Stock Exchange (IDX) for the period 2019-2022. The method used in this research is a quantitative method. The population of the study consists of companies included in the LQ-45 group and listed on the IDX from 2019 to 2022. The sample was determined using the purposive sampling method, with a population of 45 companies, resulting in a sample of 19 companies, and thus, the research data amounts to 76 data points. The data used in this study are quantitative data collected through documentation methods via the official IDX website: www.idx.co.id. The results of the study indicate that, based on simultaneous testing (F test), there is a significant effect of the variables Dividend Policy (X1), Debt Policy (X2), and Profitability (X3) simultaneously on Firm Value (Y). However, based on partial testing (t test), the Dividend Policy (X1) variable does not have a significant effect on Firm Value (Y), the Debt Policy (X2) variable does not have a significant effect on Firm Value (Y), and Profitability has a significantly positive effect on Firm Value (Y).